The Relationship Between Husband Support And Compliance Of Pregnant Mothers In Undergoing Triple Elimination Examination In 2024 - Ida Ayu Sri Darmayanthi; I Nyoman Wirata; Gusti Ayu Tirtawati (Jurnal EduHealth, 2025)
The program aimed at achieving and maintaining the elimination of infectious diseases such as HIV, Syphilis, and Hepatitis B from mother to baby to achieve better health through a coordinated approach is called triple elimination.Based on the interviews conducted, out of 10 pregnant women who visited UPTD Puskesmas II, Denpasar Utara District Health Office, it was found that seven pregnant women did not comply with the triple elimination examination.The purpose of this study is to determine the relationship between spousal support and the compliance of pregnant women in undergoing triple elimination tests.The research was conducted at UPTD Puskesmas II, Denpasar Utara District Health Office, in March-April 2024.This research is an analytical observational study using a cross-sectional design.The data collection for this research was conducted by distributing questionnaires.The respondents were 38 pregnant women.Data analysis used univariate and bivariate methods with the Chi Square test at a significance level of p<0.05.The research results show that 32 pregnant women (84.2%) received support from their husbands in carrying out the triple elimination test, and 32 pregnant women (84.2%) complied with the triple elimination test.Statistical tests yielded a p-value of 0.000 < 0.05, which can be concluded to indicate a significant relationship between spousal support and the compliance of pregnant women in undergoing triple elimination tests.Healthcare workers are expected to enhance efforts in providing integrated pregnancy care to pregnant women who seek prenatal services at healthcare facilities.